FORMER INHABITANTS OF THE CITY OF BUENOS AIRES. XVIII AND XIX CENTURIES - Cristian Redi (European Scientific Journal, ESJ, 2012)
This paper constitutes a part of deeper research whose object of study are the former inhabitants of the city of Buenos Aires. Men and women come in spotlight when studying the basic needs of the population such as job, housing and family. With the passing of time the success or failure in the reproduction and settling (unwanted pregnancy, lack of stable income) as well as structural problems (high infant mortality rates, militarization) caused a series of adaptations in families that would lead to the acquisition of particular characteristics. Although census permit to identify population; in order to investigate the causes, changes and adaptations in the family forms in time I have used two analytical categories: amparo and desamparo. As well as a crossed genealogical model of analysis among the homes considered in the population records (1833 and 1855)